1865 Fla. Laws 27, An Act Prescribing Additional Penalities For the Commission of Offenses Against the State, and for Other Purposes, Chap. 1466, § 19 - (:unkn) unknown (General Publisher, 1865)
Prohibited hunting with a gun on lands without the owners permission. Violators guilty of a misdemeanor.
--
Keywords: HUNTING REGULATION